Factors influencing the implementation of person-centred care in nursing homes by practice development champions: a qualitative process evaluation of a cluster-randomised controlled trial (EPCentCare) using Normalization Process Theory - Richter, Christin; Fleischer, Steffen; Langner, Henriette; Meyer, Gabriele; Balzer, Katrin; Köpke, Sascha; Sönnichsen, Andreas; Löscher, Susanne; Berg, Almuth (BMC nursing, 2022)
Background Person-centred care (PCC) has been suggested as the preferred model of dementia care in all settings. The EPCentCare study showed that an adapted PCC approach was difficult to implement and had no effect on prescription of antipsychotics in nursing home residents in Germany. This paper reports the qualitative process evaluation to identify facilitators and barriers of the implementation of PCC in German nursing homes from the perspective of participating practice development champions. Methods Five individual and 14 group interviews were conducted with 66 participants (staff and managers) from 18 nursing homes. The analysis was based on inductive coding to identify factors influencing the PCC implementation process. Identified factors were systematised and structured by mapping them to the four constructs (coherence, cognitive participation, collective action, reflexive monitoring) of the Normalization Process Theory (NPT) as a framework that explains implementation processes. Results Facilitating implementation factors included among others broadening of the care perspective (coherence), tolerance development within the care team regarding challenging behaviour (cognitive participation), testing new approaches to solutions as a multi-professional team (collective action), and perception of effects of PCC measures (reflexive monitoring). Among the facilitating factors reported in all the NPT constructs, thus affecting the entire implementation process, were the involvement of relatives, multi-professional teamwork and effective collaboration with physicians. Barriers implied uncertainties about the implementation and expectation of a higher workload (coherence), concerns about the feasibility of PCC implementation in terms of human resources (cognitive participation), lack of a person-centred attitude by colleagues or the institution (collective action), and doubts about the effects of PCC (reflexive monitoring). Barriers influencing the entire implementation process comprised insufficient time resources, lack of support, lack of involvement of the multi-professional team, and difficulties regarding communication with the attending physicians. Conclusions The findings provide a comprehensive and detailed overview of facilitators and barriers structured along the implementation process. Thus, our findings may assist both researchers and clinicians to develop and reflect more efficiently on PCC implementation processes in nursing homes. Trial registration ClinicalTrials.gov identifier: NCT02295462 ; November 20, 2014.